Preparing Generation Z for the Future Workforce: The Interplay of Digital Literacy and Sustainable Mindset - Tri Murwaningsih; Yosep Tegar Prameswara; Hani Febriyanti; Az-Zahra Ayu Permata; Arvano Sahwa Riordan; Ali Abdi Hassan; Nidhoil Mohamed Ibrahim (Jurnal Pendidikan Progresif, 2026)
This study aims to analyse the influence of digital literacy and a sustainable mindset on the work readiness of vocational high school students. This study used a quantitative approach with Partial Least Squares-Structural Equation Modelling (PLS-SEM) as the analytical technique. This study focuses on students of public vocational high schools in Surakarta, with a total of 306 respondents, of whom 287. Data collection was conducted using a closed questionnaire with a 1-5 Likert scale. The research instrument was adapted from previous studies, then tested for validity and reliability. The results of the hypothesis test indicate that digital literacy has a positive and significant effect on students' work readiness (t-statistic = 9.307, p = 0.000). These findings indicate that students with good digital literacy tend to feel more prepared to enter the world of work. In addition, a sustainable mindset was also found to have a positive and significant effect on the work readiness of vocational high school students (t-statistic = 7.265, p = 0.000). These findings indicate that awareness and a sustainable mindset are becoming increasingly relevant competencies in the modern workplace. These findings confirm that students' digital literacy can influence their work readiness. Not only that, but students' awareness of a sustainability mindset also influences their work-readiness. Based on these findings, vocational schools are advised to consistently focus on digital literacy through technology-based learning and to instill sustainability values through environmentally oriented school projects or activities. An introduction to sustainability values is necessary, given the increasing attention from government and industry to environmental sustainability. Keywords: digital literacy, Generation Z, sustainable mindset, vocational school, work readiness.